Pigeonhole notification system by utilizing telegram messenger - Mohamad Eliyass, Jamaruppin (2014)
Pigeonhole Notification System by Utilizing Telegram Messenger is one system was built using simple embedded system and Telegram Messenger one type of mobile messaging client. Pigeonhole Notification System by Utilizing Telegram Messenger is aim to help Faculty of Computer Systems & Software Engineering (FSKKP) lecturers to get notification about the present of mails into their pigeonholes. In addition, this system also will give warning notification if the volumes of their pigeonhole already reach certain level of fullness. Every notification will directly sent to user Telegram Messenger account and user will access in multiple platform depends on user devices such as Android base device, Windows base device, OS X base device, or Linux base device.